2009
DOI: 10.1159/000213057
|View full text |Cite
|
Sign up to set email alerts
|

Barriers, Legal Issues, Limitations and Ongoing Questions in Telemedicine Applied to Stroke

Abstract: The use of telemedicine services, such as telestroke, is still highly fragmented and its deployment in an integrative healthcare system is challenging. Factors impeding the growth of telemedicine include confidence and malpractice issues, technical advances, reimbursement, licensing, credentialing costs, cost effectiveness, and legal issues. These barriers, limitations and requirements in the routine use of telemedicine are reviewed, in addition to medical activities, the objectives of telestroke, technical as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 25 publications
0
9
0
3
Order By: Relevance
“…On the spoke level, Rogove et al [ 30 ] found that lack of leadership support was a major barrier to telestroke, thus emphasizing the enabling role of “managerial telestroke championship.” O'Toole Jr. et al [ 29 ] identified the lack of “local neurological expertise” in rural areas as a major barrier to telestroke adoption and implementation. Other studies have pointed to the need for “continuous telestroke process improvement.” For example, Medeiros de Bustos et al [ 51 ] identified the lack of predefined procedures and uneven standards of evaluating stroke care quality as major challenges to telestroke utilization, and Gogan and Garfield [ 50 ] identified the need to create appropriate checklists and protocols for stroke care and to engage users in developing repeatable processes. Interestingly, although many studies point to the general need for internal and external coordination for stroke care [ 29 , 52 ], few studies have examined the role of a stroke committee of key stakeholders in directing such efforts or of a dedicated telestroke coordinator in facilitating day-to-day stroke delivery.…”
Section: Discussionmentioning
confidence: 99%
“…On the spoke level, Rogove et al [ 30 ] found that lack of leadership support was a major barrier to telestroke, thus emphasizing the enabling role of “managerial telestroke championship.” O'Toole Jr. et al [ 29 ] identified the lack of “local neurological expertise” in rural areas as a major barrier to telestroke adoption and implementation. Other studies have pointed to the need for “continuous telestroke process improvement.” For example, Medeiros de Bustos et al [ 51 ] identified the lack of predefined procedures and uneven standards of evaluating stroke care quality as major challenges to telestroke utilization, and Gogan and Garfield [ 50 ] identified the need to create appropriate checklists and protocols for stroke care and to engage users in developing repeatable processes. Interestingly, although many studies point to the general need for internal and external coordination for stroke care [ 29 , 52 ], few studies have examined the role of a stroke committee of key stakeholders in directing such efforts or of a dedicated telestroke coordinator in facilitating day-to-day stroke delivery.…”
Section: Discussionmentioning
confidence: 99%
“…To allow breakthrough results, several issues still need to be tackled, including data security, privacy, medical device regulations, liability on product failure and reimbursement [44,73]. …”
Section: New Developments and Future Conceptsmentioning
confidence: 99%
“…However, the system generates immediate costs which have been poorly assessed to date. Moreover, as these charges are mainly attributed to the spokes, many hospitals are reluctant to become “rt-PA capable” centers representing a hurdle to the implementation of telestroke ( 6 , 7 ). The answer to this dilemma could be the application of an economic model regulating the financial flow between a hub and its spokes but this has never been reported before.…”
Section: Introductionmentioning
confidence: 99%